A video-oculography study of fixation instability in myasthenia gravis - Nguyen, Elle Minh Ngoc Le; Clough, Meaghan J.; Fielding, Joanne; White, Owen B. (Frontiers in Neurology, 2025)
IntroductionMyasthenia gravis (MG) is an autoimmune disease that causes extraocular muscle weakness in up to 70–85% of patients, which can impact quality of life. Current diagnostic measures are not very sensitive for ocular MG. This study aimed to compare fixation instability (inability to maintain gaze on a target) in patients with MG with control participants using video-oculography.MethodsA prospective study of 20 age-and sex-matched MG and control participants was performed using a novel protocol with the EyeLink 1000 plus ©. Bivariate contour ellipse area (BCEA) analysis, number of fixations on a target, and percentage of dwell time of fixations in the target interest area (IA) were calculated. Inter-eye (right vs. left) comparisons were performed using paired t-tests, and inter-group (MG vs. control) comparisons were performed using independent samples t-tests.ResultsThere were no inter-eye differences in the BCEAs between control eyes and MG eyes. However, the BCEAs were larger in both the right (RE) and left (LE) eyes of MG patients in the right (RE p = 0.029, LE p = 0.033), left (RE p = 0.006, LE p = 0.004), upward (RE p = 0.009, LE p = 0.018), and downward (RE p = 0.006, LE p = 0.006) gaze holds of the controls. The total mean sum of gaze hold fixations in all directions was greater in MG patients than in control participants (354 ± 139 vs. 249 ± 135, p = 0.020), with horizontal gaze holds showing greater differences than vertical gaze holds (p = 0.007 vs. p = 0.097). The percentage of dwell time in the target IA was lower in MG patients, but this only reached significance in the right gaze hold (p = 0.003).ConclusionMG patients showed greater BCEA values and refixations and lower target IA percentages of dwell time during gaze hold than control participants, suggesting extraocular neuromuscular junction instability and fatigue. Interestingly, there were no significant inter-eye differences in MG participants. This study is limited by the small number of patients but adds to the current literature exploring video-oculography in MG patients as a novel diagnostic tool. Further studies are recommended for translation into clinical practice.